Compressive sensing based joint frequency offset and channel estimation for OFDM - Senyuva, Rifat Volkan; Karabulut-Kurt, Günes; Anarim, Emin (Springer Science and Business Media LLC, 2016)
Nous considérons l'estimation conjointe du décalage de fréquence porteuse (CFO) et de la réponse impulsionnelle de canal (CIR) pour le multiplexage par répartition orthogonale de la fréquence (OFDM) avec des symboles pilotes. Une nouvelle méthode basée sur la détection comprimée est proposée. Il a été montré que le CIR peut être représenté comme un signal clairsemé d'un bloc en utilisant un dictionnaire construit en concaténant des sous-espaces de valeurs CFO prises à partir d'un espace de recherche. La récupération du CFO et du CIR est accomplie par l'algorithme de poursuite de correspondance orthogonale de bloc. Le procédé proposé utilise un seul bloc d'entraînement OFDM et ne nécessite aucune initialisation. La performance de la méthode proposée est comparée aux estimateurs pilotes bien établis : Moose, Classen, l'estimateur du maximum de vraisemblance et l'algorithme p. Les résultats numériques montrent que la performance de la méthode proposée ne dépend pas de la valeur du directeur financier. Nous donnons également les limites supérieures du pire des cas pour l'erreur quadratique moyenne de l'estimation du CIR pour un canal à trajets multiples clairsemé.

Consideramos la estimación conjunta del desplazamiento de frecuencia portadora (CFO) y la respuesta al impulso del canal (CIR) para la multiplexación por división de frecuencia ortogonal (OFDM) con símbolos piloto. Se propone un nuevo método basado en la detección comprimida. Se ha demostrado que el CIR se puede representar como una señal dispersa de 1 bloque utilizando un diccionario construido concatenando subespacios de valores CFO tomados de un espacio de búsqueda. La recuperación tanto del CFO como del CIR se logra mediante el algoritmo de búsqueda de coincidencias ortogonales de bloques. El método propuesto utiliza solo un bloque de entrenamiento OFDM y no requiere ninguna inicialización. El rendimiento del método propuesto se compara con los estimadores basados en pilotos bien establecidos: Moose, Classen, el estimador de máxima verosimilitud y el algoritmo p. Los resultados numéricos muestran que el rendimiento del método propuesto no depende del valor del CFO. También damos los límites superiores del peor de los casos para el error cuadrático medio de la estimación de CIR para un canal de trayectos múltiples disperso.

We consider joint estimation of carrier frequency offset (CFO) and channel impulse response (CIR) for orthogonal frequency division multiplexing (OFDM) with pilot symbols. A new method based on compressed sensing is proposed. It has been shown that the CIR can be represented as a 1-block sparse signal by using a dictionary constructed by concatenating subspaces of CFO values taken from a search space. Recovery of both CFO and CIR is accomplished by the block orthogonal matching pursuit algorithm. The proposed method uses only one OFDM training block and does not require any initialization. The performance of the proposed method is compared against the well-established pilot based estimators: Moose, Classen, the maximum likelihood estimator, and the p-algorithm. Numerical results show that the performance of the proposed method does not depend on the value of the CFO. We also give worst-case upper bounds for the mean squared error of the CIR estimate for a sparse multipath channel.

نحن نعتبر التقدير المشترك لإزاحة تردد الناقل (CFO) واستجابة نبض القناة (CIR) لمضاعفة تقسيم التردد المتعامد (OFDM) مع الرموز التجريبية. تم اقتراح طريقة جديدة تعتمد على الاستشعار المضغوط. وقد تبين أنه يمكن تمثيل سجل المعلومات الائتمانية كإشارة متفرقة من كتلة واحدة باستخدام قاموس تم إنشاؤه من خلال تسلسل المساحات الفرعية لقيم المدير المالي المأخوذة من مساحة البحث. يتم استرداد كل من المدير المالي و CIR من خلال خوارزمية السعي للمطابقة المتعامدة. تستخدم الطريقة المقترحة كتلة تدريب OFDM واحدة فقط ولا تتطلب أي تهيئة. تتم مقارنة أداء الطريقة المقترحة مقابل المقدرين التجريبيين الراسخين: موس، كلاسن، مقدر الاحتمال الأقصى، والخوارزمية p. تظهر النتائج العددية أن أداء الطريقة المقترحة لا يعتمد على قيمة المدير المالي. نعطي أيضًا الحدود العليا في أسوأ الحالات لمتوسط الخطأ التربيعي لتقدير CIR لقناة متفرقة متعددة المسارات.
Keywords: Computer Networks and Communications; Computational Mechanics; Geometry; Estimator; Sparse Approximation; Engineering; Compressed Sensing; FOS: Electrical engineering, electronic engineering, information engineering; FOS: Mathematics; Orthogonal Matching Pursuit; Channel Estimation; Electrical and Electronic Engineering; Initialization; Carrier frequency offset; Frequency offset; Architectural engineering; Statistics; Orthogonal frequency-division multiplexing; Theory and Applications of Compressed Sensing; Computer science; Sparse Sensing; Computer Science Applications; Programming language; Algorithm; Joint (building); Channel (broadcasting); Physical Sciences; Signal Processing; Computer Science; Matching pursuit; Telecommunications; Compressed sensing; Multiple-Input Multiple-Output Orthogonal Frequency Division Multiplexing; Block (permutation group theory); Mathematics; Array Processing for Signal Localization and Estimation